Insight into the leavening process and structural properties of buns containing okara - Caporizzi Rossella; Derossi Antonio; Speranza Barbara; Racioppo Angela; La Gatta Barbara; Rutigliano Mariacinzia; Marinaro Grazia; Di Ruzza Benedetto; Cammarelle Antonella; Viscecchia Rosaria; Corbo Maria Rosaria; Severini Carla (Applied Food Research)
The incorporation of food by-products into bakery formulations offers a promising approach to enhancing nutritional value and promoting sustainability. This study evaluates the effects of okara, a soy-processing by-product, on the technological and structural properties of leavened bakery products. Dough formulations were prepared with 5 % and 10 % okara powder substitution and leavened using Saccharomyces cerevisiae alone or in combination with Lactiplantibacillus plantarum. The results revealed that okara addition influenced dough leavening capacity, with higher incorporation levels reducing gas retention due to gluten network dilution, and increased protein content. However, buns formulated with 5 % okara maintained acceptable proofing performance and overall quality. Physicochemical analysis indicated that okara altered water content and activity during storage of enriched buns, along with increased crust browning due to intensified Maillard reactions. Textural properties remained largely unchanged, except for chewiness, which slightly increased, while microstructural analysis confirmed a denser crumb structure with reduced pore size and connectivity. Consumer analysis demonstrated a positive willingness to purchase okara-enriched buns, with education and gender significantly influencing purchase intent. These findings highlight the potential of okara as a functional ingredient in bakery products, supporting food waste valorization and dietary diversification. Future research should explore process optimization and sensory profiling to enhance consumer appeal and product performance.